2007
DOI: 10.1021/ef070061j
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Upgrading Processes on Combustion Characteristics of Berau Coal

Abstract: Indonesian coal was upgraded by upgraded brown coal (UBC), hot water drying (HWD), and steam drying (SD) processes to study the combustion characteristics of this coal. The differential thermal-thermogravimetric analysis (DTA-TG) was carried out to obtain some combustion parameters, such as, ignition temperature (T ig ), maximum combustion rate temperature (T max ), maximum combustion rate (R max ), char burn-out temperature (T bo ), and ash yield. The differential thermal analyzer (DTA) curve can be used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 6 publications
0
23
0
Order By: Relevance
“…They found that T i of the upgraded coals increased, whereas T max is not so changed, and k max significantly increased. They also treated the brown coal with hot water drying (HWD) and steam drying (SD), and the combustion characteristics of HWD and SD processes were much better than those of the UBC process due to it conducted at lower temperature and pressure [36]. Besides, there were three DTG peaks for all of the brown coals in their study.…”
Section: Influence Of Upgrading On Coal Combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that T i of the upgraded coals increased, whereas T max is not so changed, and k max significantly increased. They also treated the brown coal with hot water drying (HWD) and steam drying (SD), and the combustion characteristics of HWD and SD processes were much better than those of the UBC process due to it conducted at lower temperature and pressure [36]. Besides, there were three DTG peaks for all of the brown coals in their study.…”
Section: Influence Of Upgrading On Coal Combustionmentioning
confidence: 99%
“…This result demonstrates that several volatile matters turned into char structures during the upgrading process, thus enhancing the char combustion process. Besides, there was another combustion peak around 300 C for ZT-250, which was ascribed to the combustion of volatile matter [35,36] due to its highest volatile matter content (35.58 wt%, Table 1). This provided another evidence that some unstable active compositions in the volatile matter gradually transferred into stable inert components.…”
Section: Influence Of Upgrading On Coal Combustionmentioning
confidence: 99%
“…Low-rank coal inherently has many disadvantages for direct application in preconstructed power plants, such as low heating value, low combustion efficiency in the boiler, high shipping cost due to moisture readsorption, and the increase of carbon dioxide emission. For these reason, energy companies are still sometimes hesitant to adopt low-rank coal as fuel. , High moisture content in the low-rank coal, in particular, causes spontaneous combustion during its transportation and storage. , Hence, there have been great efforts to develop the low-rank coal upgrading technologies. , It has been reported that dewatering and prevention of water readsorption into the coal play a key role to improve low-rank coal in terms of heating value and transportation price. , The Korea Institute of Energy Research has proposed an upgraded low-rank coal called HCK, which is a fuel synthesized by the impregnation of bioliquid into low-rank coal followed by torrefaction. First, they suggested molasses as a bioliquid additive.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 High moisture content in the low-rank coal, in particular, causes spontaneous combustion during its transportation and storage. 8,9 Hence, there have been great efforts to develop the low-rank coal upgrading technologies. 10,11 It has been reported that dewatering and prevention of water readsorption into the coal play a key role to improve low-rank coal in terms of heating value and transportation price.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Various dewatering and upgrading processes have been developed since the 1920s, such as the upgraded brown coal (UBC) method, hot water drying (HWD) method, steam drying (SD) process, microwave irradiation process, and solvent extraction process. The general conclusions of the LRC upgrading process are basically known. Several scientific researchers found that Indonesian coal upgraded by UBC, HWD, and SD processes has a higher T i , T max , R max , and calorific value. ,, The oxygen content and moisture of upgraded LRCs decrease, whereas their calorific value increases. , Similar conclusions were shown in upgraded coal by solvent extraction at around 350 °C. , Some researchers investigated the effects of the pore structure and oxygen functional group content on the moisture distribution and found that the removal of free moisture is associated with the collapse of macropore structures, whereas the bound water is reduced because of the removal of oxygen functional groups . Besides, the effects of desulfurization, enhancement of grindability on LRCs, ,, and increase of the rheological characteristics of coal slurries are obtained in the microwave irradiation upgrading process. , …”
Section: Introductionmentioning
confidence: 99%